IMPROVING DESCRIPTIVE WRITING SKILL THROUGH CONTEXTUAL APPROACH IN 4 GRADERS OF ELEMENTARY SCHOOL OF 1 PADAAN - Ika Nurwulandari; Anna Mariyani (IKIP Siliwangi, 2020)
The success of teaching and learning process is largely determined by students’ ability to write. However, most teachers still apply inappropriate teaching method, so this is important to find a new innovations in teaching. One of them is through contextual approach. This study aims to find out whether contextual approach can improve the 4th graders’ descriptive writing skills or not. This is a classroom action research in the form of collaboration between researchers and class teachers. the data source used was information data from the people as participants. They are 4th graders teacher, students' daily test scores, observations of the learning process using contextual approach, and other information about the school and its history. To test the validity of the data the writer uses triangulation. The analysis technique used is data reduction, data presentation, and drawing conclusions. The result of the study shows that the contextual approach can improve 4th graders descriptive writing skills of SDN 01 Padaan, Japah, Blora in the academic year of 2019/2020.Keywords: descriptive writing, contextual approach